Methods Of Developing Critical Thinking By Critically Assessing The Characters Of The Work (Texas Journal of Philology, Culture and History, 2024)
This article reflects on the possibilities of designing lessons aimed at organizing a critical assessment of the personality of the heroes of a work,in addition to the formation of students ' critical thinking and the development of konikmas of critical assessment of the heroes of the work,the analysis and translation of artistic texts, as well as many positive qualities.